Diagnostic Accuracy of CRP (C-Reactive Protein) Examination in Neonatal Infections - M. Sholeh Kosim; Bagus Ngurah Putu Arhana; Harry Mangunsong (Paediatrica Indonesiana, 1993)
The incidence of neonatal infections has been still high in Indonesia. The main factors influencing success of treatment are early clinical diagnosis and rapid determination of the etiologic microorganisms. C-reactive protein (CRP) could be measured in the serum of baby suffering from bacterial infections. The aim of this study was to compare the capability of CRP examination in determining the diagnosis of neonatal infections, using blood culture examination as the gold standard. For comparison, white blood cell (WBC) and platelet counts, which have been used as indicators of neonatal infections, were also evaluated. This study was done prospectively on 30 cases with suspected neonatal infections admitted to the High Risk Baby Ward, Division of Perinatology, and 30 normal babies as control, during the period of April to December 1990. CRP examination was done by latex agglutination method. The results of this study revealed that CRP examination has good sensitivity, specificity. and predictive values. CRP was also proved to be superior to WBC and platelet counts. CRP examination was also easy to perform, cheaper, and faster than blood culture examination. It is concluded that CRP examination could be used as the confirmatory tool in the diagnosis of neonatal bacterial infections.